The Nomogram of Penile Length and Circumference in Iranian Term and Preterm Neonates - Soheilipour, Fahimeh; Rohani, Farzaneh; Dehkordi, Elham Hashemi; Isa Tafreshi, Roya; Mohagheghi, Parisa; Zaheriani, Seyed-Mohammadsalar; Jesmi, Fatemeh; Salehiniya, Hamid (Frontiers in Endocrinology, 2018)
Background and objectives The normal length of penis in preterm and term neonates is different among different nations, and is affected by various factors. The present study aimed to determine stretched penile length (SPL) values and cutoff level of micropenis in term and preterm Iranian neonates, for the first time. Materials and methods All male neonates born in two general hospitals of Tehran (Akbarabadi, and Rasoul hospitals), center of Iran, with gestational age of 28–42 weeks were included and their SPL and penile circumference (PC) were examined on the first 3 days after birth by the same physician. Birth weight (BW), and height, gestational age, type of delivery, mother’s age, twin/multiple pregnancy, drug, and medical history of mother during pregnancy were recorded and cutoff levels of two variables were calculated based on the collected variables for different gestational ages. Results Among a total of 587 neonates, 203 neonates were born term and 384 preterm. Mean ± SD of neonates’ BW were 2,682.51 ± 739.30 (850–4800) gr. Mean ± SD of their SPL was 22.48 ± 3.34 mm; 25.92 ± 1.54 mm in term and 20.66 ± 2.50 mm in preterm infants (P = 0.001). Mean ± SD of PC was 6.71 ± 1.31 mm; 8.14 ± 0.48 in term and 5.96 ± 0.92 in preterm infants (P = 0.001). SPL and PC were significantly correlated with type of delivery, number of parity, gestational age, BW, and crown-heel length, head circumference (P < 0.001). Conclusion This study suggested that SPL in male neonates was 22.48 mm and PC was 6.71 mm, both correlated with gestational age and BW. Due to the ethnical variety of this cutoff points and lack of an appropriate study in Iran, these cutoff points can be used by all physicians as a reference for Iranian newborns (term and preterm), in order to prevent misdiagnosis of micropenis and genital disorders.